2002
DOI: 10.1097/00000539-200211000-00020
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of the Face, Legs, Activity, Cry, Consolability Observational Tool as a Measure of Pain in Children with Cognitive Impairment

Abstract: The FLACC pain assessment tool may facilitate reliable and valid observational pain assessment in children with cognitive impairment who cannot self-report their pain. Objective pain assessment is important to facilitate effective postoperative pain management in these vulnerable children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(136 citation statements)
references
References 9 publications
1
123
0
12
Order By: Relevance
“…8 Furthermore, the FLACC was also used with preverbal children with typical development, 15 and with children with atypical development. 13,14 One review study of behavioral measures of pain assessment submitted certain scales to a rigorous review procedure and found their levels of clinical evidence. 40 The FLACC was recommended for postoperative pain assessment, the CHEOPS for preoperative and postoperative pain assessment, and the PPPM for postoperative pain assessment on hospital discharge: three scales widely used for pain assessment, according to the levels of clinical evidence given.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 Furthermore, the FLACC was also used with preverbal children with typical development, 15 and with children with atypical development. 13,14 One review study of behavioral measures of pain assessment submitted certain scales to a rigorous review procedure and found their levels of clinical evidence. 40 The FLACC was recommended for postoperative pain assessment, the CHEOPS for preoperative and postoperative pain assessment, and the PPPM for postoperative pain assessment on hospital discharge: three scales widely used for pain assessment, according to the levels of clinical evidence given.…”
Section: Discussionmentioning
confidence: 99%
“…11 Nevertheless, in the course of this literature review it was found that ordinal scales are also used by trained observers or by the medical and nursing teams to assess child pain. In these cases the following instruments were used: the Objective Pain Scale (OPS), 8 the Faces, Leg, Activity, Cry and Consolability scale (FLACC), 8,[13][14][15] the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS), 8 the Pediatric Pain Profile (PPP), 16 the Alder Hey Triage Pain Score (AHTPS), 17 the Child Facial Coding System (CFCS) 18 and the Non-Communicating Children's Pain Checklist-Revised (NCCPC-R). 19 …”
Section: Measurement Scales Of the Instruments Analyzedmentioning
confidence: 99%
See 3 more Smart Citations